Varieties of alternative fuel in the modern world - Strukov, V. S.; Shliapina, Olesia; Шляпіна, Олеся Володимирівна; Шляпина, Олеся Владимировна (My University, 2019)
Alternative fuel is more ecological then diesel, because it does not have a negative effect on the environment.
Keywords: fuel; result of the use of the petroleum; biofuels; Natural gas